A prospective registry to get insights into profile, management and outcome of cardiogenic shock patients. (3rd October 2022) - Morici, N; Frea, S; Bertaina, M; Iannacone, M; Sacco, A; Villanova, L; Corrada, E; Valente, S; De Ferrari, G M; Ravera, A; Moltrasio, M; Sionis, A; et al.
Abstract: Background: Cardiogenic shock (CS) is the most severe form of acute heart failure, characterized by life-threatening end-organ hypoperfusion resulting from a low cardiac output state. Data on epidemiology of CS has been mostly drawn from registries focusing on acute myocardial infarction (AMI). However, recent evidence in a contemporary cohort in North America has shown that more than two thirds of all CS cases were related to causes other than AMI and that these patients had outcomes at least as poor as patients with AMICS. Purpose: To provide data on profile, management, outcome, and evolution over time of CS patients admitted to ICCU/ICU and to compare them between patients with AMICS and acute decompensated heart failure (ADHF-CS). Methods: The Altshock-2 Registry is a multicenter national prospective data collection, part of the Italian Altshock-2 program. Recruitment started on 2 March 2020 with 11 Italian Centers contributing to patients' enrolment. A total of 238 patients were hospitalized with confirmed diagnosis of CS between March 2020 and February 2022 in a multicenter national initiative. The mean age of this patient population was 64 years (interquartile range [IQR] 54–74) and 76% were male. Ninety-seven patients (41%) were admitted for AMICS, whereas 84 patients (35.3%) had ADHF-CS; 57 patients (24%) had other causes. As compared to AMICS patients, those admitted for ADHF-CS were younger, but with a higher burden of comorbidities (renal, liver, thyroid disease, atrial fibrillation, anemia), pre-existing decreased ejection fraction and a higher number of chronic drugs. Patients with ADHF-CS had a prevalent cardio-metabolic phenotype upon admission with prevalent congestion. Mechanical ventilation was more commonly used in patients with AMICS, compared to ADHF-CS, along with an increased inotropic score. Conversely, sodium nitroprusside was used in about sixty percent of patients with ADHF-CS. Sixty percent of the included population received a temporary mechanical circulatory support (MCS) device, which was intra-aortic balloon pump (IABP) in the eighty percent of the supported patients. Pulmonary artery catheter was used for monitoring only in the 18% of the included patients whereas an extensive echocardiographic approach was applied. Twenty-one patients (25%) underwent heart replacement therapy in the ADHF-CS patients versus 2 (2%) in the AMICS. Thirty-day mortality occurred in 32 patients (33%) in the AMICS group versus 23 (27%) in the ADHF-CS group (p=0.41). Conclusions: Different diagnostic approaches and uses of mechanical circulatory support devises and inotropes are implemented in transatlantic settings. Uniform definitions and more homogenous protocols tailored on CS etiologies and clinical and biochemical phenotypes are needed in prospective initiatives in order to effectively compared results and outcome. Funding Acknowledgement: Type of funding sources: None.